Environmental management accounting and waste management practices: A case of a manufacturing company - S. M. Chaturika Seneviratne; Gayasha Kalpani (goodwood publishing, 2020)
Purpose: This study examines how Environmental Management Accounting practices are related to waste management practices and how the organization in the case study is influenced in adopting the waste management practices Research methodology: The case study method was used in examining the applicability of Environmental Management Accounting to waste management in one large manufacturing company. Interviews, observations and archival documents were used as data collection methods. Results: The study observed that the company had reinvigorated environmental management and waste management practices due to the influence of the major stakeholders. These motivations can be categorized into three main pillars including coercive, mimetic, and normative isomorphisms. Limitations: As the research is directed towards the selection of in-depth inquiry of specific settings infused with culture, values, beliefs, stories, language, perception, politics and ideology, it might cause to diminish the researcher's analytical objectivity and independence of the research. Contribution: Policies, practices and motivations promote the future development of environmental management accounting and waste management practices in the Sri Lankan context.